Rove Beetles of the Genus Gyrophaena (Coleoptera, Staphylinidae, Aleocharinae) of Ukraine - Glotov, S.V.; Petrenko, A.A.; Mateleshko, A.Yu. (Вестник зоологии, 2011)
Twenty species of the genus Gyrophaena Mannerheim, 1830, from Ukraine are reviewed. Of these, five species: G. joyi Wendeler, 1924; G. joyioides Wüsthoff, 1937; G. orientalis A. Strand, 1938; G. pseudonana A. Strand, 1939 and G. williamsi A. Strand, 1935, are recorded from Ukraine for the first time. Detailed morphological descriptions, data on bionomics and distribution are given for each species. A key to all subgenera and species of the genus Gyrophaena occurring in Ukraine is provided. Дан обзор 20 видов рода Gyrophaena Mannerheim, 1830 фауны Украины. Среди выявленных видов 5 (G. joyi Wendeler, 1924; G. joyioides Wьsthoff, 1937; G. orientalis A. Strand, 1938; G. pseudonana A. Strand, 1939 и G. williamsi A. Strand, 1935) впервые приведены для фауны Украины. Даны детальные морфологические описания, указаны особенности экологии и распространения для всех 20 видов. Приведена таблица для определения подродов и видов рода Gyrophaena фауны Украины.